Reading habits and interests among primary 6 pupils a study in Sekolah Kebangsaan Saints Francis Xavier Seratau Kuching Sarawak/ Diog Dios - Dios, Diog (2004)
This academic writing is conducted with the purpose to investigate the reading habits and interests among Primary 6 pupils of Sekolah Kebangsaan Saint Francis Xavier Seratau, Kuching, Sarawak. Factors and aspects related to reading habits and interests were highlighted. In eliciting the data for the research, a study involving a questionnaire survey was conducted on 45 respondents (25 girls and 20 boys) ofthe school. The pupil’s responses were analyzed in percentages.